The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11274-013-1465-3
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 interpolymer complex encapsulation improves heat stability of probiotic bifidobacteria

Abstract: The probiotic industry faces the challenge of retention of probiotic culture viability as numbers of these cells within their products inevitably decrease over time. In order to retain probiotic viability levels above the therapeutic minimum over the duration of the product's shelf life, various methods have been employed, among which encapsulation has received much interest. In line with exploitation of encapsulation for protection of probiotics against adverse conditions, we have previously encapsulated bifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Encapsulation of bifidobacteria in poly-(vinylpyrrolidone)-poly-(vinylacetate-co-crotonic acid) (PVP:PVAc-CA) interpolymer complex microparticles under supercritical conditions was applied by Thantsha, et al [165]. They reported that the produced microparticles had suitable characteristics for food applications and protected the bacteria in simulated gastrointestinal fluids as well as improved the shelf life for 12 weeks at 30 °C [165]. The strain B. adolescentis (ATCC 15703) was entrapped within microcapsules prepared using 10.00% ( w / w ) chickpea protein isolates cross-linked with 0.20% ( w / v ) of genipin, or in the presence of 0.20% ( w / v ) alginate or k-carrageenan.…”
Section: Strategies For Enhanced Probiotic Viabilitymentioning
confidence: 99%
“…Encapsulation of bifidobacteria in poly-(vinylpyrrolidone)-poly-(vinylacetate-co-crotonic acid) (PVP:PVAc-CA) interpolymer complex microparticles under supercritical conditions was applied by Thantsha, et al [165]. They reported that the produced microparticles had suitable characteristics for food applications and protected the bacteria in simulated gastrointestinal fluids as well as improved the shelf life for 12 weeks at 30 °C [165]. The strain B. adolescentis (ATCC 15703) was entrapped within microcapsules prepared using 10.00% ( w / w ) chickpea protein isolates cross-linked with 0.20% ( w / v ) of genipin, or in the presence of 0.20% ( w / v ) alginate or k-carrageenan.…”
Section: Strategies For Enhanced Probiotic Viabilitymentioning
confidence: 99%
“…For example, Thantsha et al. (2014) used polyvinylpyrrolidone and vinylacetate‐ co ‐crotonic acid, both of which can be plasticized in supercritical CO 2 to form an interpolymer complex though hydrogen bonding, to encapsulate B. lactis Bb12 and B. longum Bb46. The prepared probiotic powders with a w of 0.25–0.43 showed more than 6 log CFU/g viability after 12‐week storage at 30°C.…”
Section: Methods Of Producing Powdered Probioticsmentioning
confidence: 99%
“…Supercritical technology is another novel method to prepare probiotic powders by immobilizing probiotics in interpolymer complexes formed in supercritical CO 2 as the solvent, and the subsequent depressurization removes CO 2 to form dry microcapsules (Liu et al, 2019). For example, Thantsha et al (2014) used polyvinylpyrrolidone and vinylacetateco-crotonic acid, both of which can be plasticized in supercritical CO 2 to form an interpolymer complex though hydrogen bonding, to encapsulate B. lactis Bb12 and B. longum Bb46. The prepared probiotic powders with a w of 0.25-0.43 showed more than 6 log CFU/g viability after 12-week storage at 30 • C. However, electrospinning, electrospray-assisted drying, and supercritical technology may not meet the production scale required for food manufacturing.…”
Section: Other Low Temperature Drying Methodsmentioning
confidence: 99%
“…They showed that co-encapsulation of prebiotic resistant starch corns had a negative influence on the physical barrier of the protein matrix, leading to a decrease of the protective effect of the probiotic (Heidebach et al, 2010). Thantsha et al (2014) used poly-(vinylpyrrolidone)-poly-(vinyl acetate-co-crotonic acid) for encapsulation of B. lactis Bb12 and B. longum Bb46 under supercritical conditions. They described that microparticles were able to protect the bacteria in simulated gastrointestinal fluids as well as to improve the lifetime of storage for 12 weeks at 30 • C. Wang et al (2014) reported on the entrapment of B. adolescentis ATCC 15703 preparing microcapsules using 10% of chickpea protein isolates crosslinked with 0.20% of genipin, or in the presence of 0.10% of alginate.…”
Section: Microencapsulationmentioning
confidence: 99%